Crescimento do emprego nas firmas da economia brasileira: Resultados por grupos de idade e tamanho - Danilo Santa Cruz Coelho; Carlos Henrique Corseuil; Miguel N. Foguel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Using microdata of Brazilian firms from a longitudinal matched employee-employer data set (Rais) in the period from 1993 to 2013, this paper confirms that the middle part of the size distribution is "missing" in Brazil and apparently this feature is more intense than in other countries for which there are available results. Our analysis of the dynamics of employment over the life cycle of establishments provides some clues on why there is a missing middle in the size distribution. Considering a representative establishment, the results show that it is born small (perhaps too small) and that the pattern of the growth rate over its life cycle imposes a long time span to surpass the threshold of a mid-sized plant. Our results also indicate that age effects are the main component that explains the life cycle pattern of establishments. This result comes from the application of Deaton and Paxons (1994) decomposition method, which shows limited influence of year effects and birth-cohort effects.
Keywords: O14; O12; L25; L26; 330; firm growth; firm size distribution; age-time-cohort decomposition; missing-middle